The Effect of CSR Expenditure on Corporate Financial Performance with Green Innovation as a Mediating Variable - Tata Persada; Ernie Hendrawaty (Electronic Journal of Education, Social Economics and Technology, 2025)
Corporate social responsibility is designed to provide benefits to both society and the environment. With the advancement of globalization, companies are increasingly adopting sustainability strategies or green innovation to maintain their existence and public image. One such effort includes participating in the PROPER rating program to attract stakeholder interest. This indicates that investment in CSR and green innovation serves as a strategy to achieve better profitability and competitiveness. This study’s targets is to examine the relationship among CSR expenditure affects financial performance, using green innovation as a mediating variable. A sample of every firm listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period is used in this study. This study looks at both direct and indirect effects using EVIEWS 12 software to execute path analysis. The finding show that CSR expenditure has a positive influence on corporate financial performance. Additionally, CSR expenditure does not significantly influence green innovation, thereby breaking the mediating path. Consequently, the relationship among CSR expenditure and corporate financial performance is not mediated by green innovation.